Infective Endocarditis with Multiple Valvar Vegetation in Uncorrected Tetralogy Fallot: A Case Report of Rare Condition - Charlotte Johanna Cool; Eliza Techa Fattima; Mega Febrianora; Aninka Saboe (International Journal of Integrated Health Sciences, 2021)
Objective: To describe a case of an adult patient with uncorrected Tetralogy of Fallot (TOF) who suffered from Infective Endocarditis (IE) that involved the tricuspid and aortic valves.Methods: On October 2019, a-twenty-year-old male with uncorrected TOF was admitted to the emergency department of Dr. Hasan Sadikin General Hospital with a chief complaint of fever. The echocardiography showed the presence of vegetation on the tricuspid valve and aortic valve. The patient was given empirical antibiotics therapy for IE treatment. The serial blood cultures did not yield any organism growth and the transthoracic echocardiography evaluation showed healed vegetation after 21 days of antibiotics treatment.Results: A high turbulence in small VSD and valvular stenosis, as found in TOF, can injure the endocardial surface. While bacterial adherence to the injured endocardial surface can cause IE, no specific criteria available for diagnosing IE in congenital heart disease (CHD) patients compared to other population. In CHD patients, it is necessary to consider the diagnosis of IE presenting with signs of infection or fever. Our patient was known to have uncorrected TOF and was admitted to the hospital with a chief complaint of fever. The uncorrected TOF was complicated by an unusual form of aggressive vegetation involving multiple valves.Conclusion: The incidence of IE in uncorrected TOF is around 4%. Patient is  advised to receive a corrective surgery for the cardiac anomaly. Surgical repair of CHD with no residual lesion reduces the risk of IE.